47 Endothelial progenitor cells contribute to vascular repair in the ischaemic retina. Issue 20 (23rd September 2011) - Medina, R J; O'Neill, C L; O'Doherty, T M; Guduric-Fuchs, J; Gardiner, T A; Stitt, A W
Abstract : Numerous studies suggest that endothelial progenitor cells (EPCs) re-vascularise ischaemic tissues and recent clinical trials have highlighted the feasibility, safety and potential therapeutic benefit of an EPC-based cytotherapy for myocardial infarction. However there is still discrepancy about the extent to which these cells incorporate into the vasculature and the level to which they restore functionality to damaged tissue. These controversies are caused by an imprecise EPC definition as many different cell populations are collectively referred to as EPCs. Our aim was to isolate a distinct EPC population named Outgrowth Endothelial Cells (OECs) and test them as a novel cell therapy for ischaemic retinopathy. OECs were isolated from adult human peripheral blood and grown on collagen substrate. They were characterised using immunophenotyping, and genome-wide transcriptomics. Angiogenic activity was assessed using multiple functional assays in vitro, and a mouse model of ischaemic retinopathy in vivo. Our data indicate that OECs possess an unequivocal endothelial phenotype and express progenitor cell markers. They have high proliferative capacity and clonogenic potential. Furthermore, OECs are able to closely interact with mature endothelial cells through adherens and tight junctions. OEC demonstrate de novo tubulogenic potential and fully incorporate into a mature vascular network. This is also demonstrated in vivo, where OECs directly incorporate into resident ischaemic vasculature, and significantly decreased avascular areas (p<0.001) when compared to vehicle-injected retinas. In conclusion, OECs are a distinct EPC sub-population that directly contributes to vascular repair of the ischaemic retina, and have great potential as an alternative treatment for ischaemic retinopathies.